Homeownership and job-match quality in France. Issue 5 (27th May 2020) - Brunet, Carole; Havet, Nathalie
Abstract: Our empirical study stems from previous research on the inter-relations between residential status and microeconomic labor market outcomes. It focuses on employees and assesses the a priori ambiguous effect of homeownership on job-match quality. We use the French data set of the 1995–2001 European Community Household Panel to build a subjective measure of job downgrading. We estimate a recursive trivariate probit with partial observability that simultaneously models the residential status choice, its impact on the probability of being downgraded, and the selection into employment. Taking into account, the double selection process, into employment and into homeownership, and controlling unobserved individual heterogeneity, we find that private renters have between 30% and 40% higher probability of subjective downgrading than homeowners. Mortgage constraints increase the downgrading probability, but their effect is of a limited scope (around +2% percentage points for mortgagers compared with outright owners). We show that these results are robust to various specifications and instruments choice. Consequently, homeownership seems not to be associated to some harmful effects on the job-match quality. Our conclusions are consistent with recent microeconometric studies which call into question Oswald's hypothesis.